Corporate Social Responsibility and its Impact on the Market Value of Firms —— Evidence from Manufacturing Companies in China - Liang, ChongWen (2020)
Since the 20th century, the implementation of sustainable development strategies by enterprises has become an international consensus. This means that corporate social responsibility as a basic idea for constructing corporate sustainable development strategies is not only a moral obligation for enterprise, but also related to the survival and development of company. China as the "world factory" manufacturing industry is the mainstay of the Chinese economy. It has brought a series of social problems in the process of long-term development, which makes people pay more and more attention to the fulfillment of corporate social responsibilities in the manufacturing industry. Therefore, this article uses the Chinese manufacturing listed companies listed on the A-share market in 2009-2019 as a research sample and uses Stata to establish a multiple regression model to explore the impact of corporate social responsibility on corporate market value. Secondly, it also compares and discusses the impact of the social responsibility of state-owned enterprises and private enterprises on the market value of enterprises. The research results show that the corporate social responsibility commitments to primary stakeholders (shareholders, creditors, employees, consumers and governments) have a significant positive impact on the company’s market value. Meanwhile, compared with state-owned enterprises, the social responsibility of private-owned enterprises is more sensitive to the promotion of market value. Finally, based on the results, this article proposes recommendations from both the enterprise and the government to better strengthen the awareness of enterprises to perform social responsibilities, thereby enhancing the market value and promote the sustainable development of enterprises.